Folate-mediated one-carbon metabolism: a targeting strategy in cancer therapy. Issue 3 (March 2021) - Yang, Chengcan; Zhang, Jifa; Liao, Minru; Yang, Yushang; Wang, Yuxi; Yuan, Yong; Ouyang, Liang
Highlights: Cellular metabolism is reprogrammed to support tumorigenesis. Folate fulfill many metabolic requirements of proliferating cells and relevant metabolic pathway affect redox homeostasis. Folate metabolizing enzyme are regulated by variety effectors in cancer. Inhibitor of specific folate metabolizing enzyme may act as promising therapeutic agent in cancer. Abstract : Folate-mediated one-carbon metabolism (FOCM) supports vital events for the growth and survival of proliferating cells. Nucleotide synthesis and DNA methylation are the biochemical bases of cancers that are highly dependent on FOCM. Recent studies revealed that FOCM is connected with redox homeostasis and epigenetics in cancer. Furthermore, folate-metabolizing enzymes, such as serine hydroxymethyltransferase 2 (SHMT2) and methylenetetrahydrofolate dehydrogenase 2 (MTHFD2), are associated with the development of cancers, including breast cancer, highlighting their potential application in tumor-targeted therapy. Therefore, targeting metabolizing enzymes, especially SHMT2 and MTHFD2, provides a novel strategy for cancer treatment. In this review, we outline current understanding of the functions of SHMT2 and MTHFD2, discussing their expression, potential functions, and regulatory mechanism in cancers. Furthermore, we discuss examples of inhibitors of SHMT2 and MTHFD2.